2011
DOI: 10.1159/000328838
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Fragile X-Associated Tremor/Ataxia Syndrome Presenting with Executive Cognitive Deficits and Cerebral White Matter Lesions

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disorder that primarily affects males who are carriers of a premutation of a CGG expansion in the FMR1 gene. In Asian populations, FXTAS has rarely been reported. Here, we report the case of a Japanese FXTAS patient who showed predominant executive cognitive deficits as the main feature of his disease. In contrast, the patient exhibited only very mild symptoms of intention tremor and ataxia, which did not interfere with daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…White matter dementia is distinguished from cortical dementia, like Alzheimer’s disease, by relative normalcy of language function and declarative memory encoding while cognitive speed, executive function, and sustained attention are impaired (Filley, 1998; Prins et al , 2005). The FAB score decline of NIID cases may reflect the white matter damage, and this pattern of decline is similar to other neurological diseases with white matter damage, such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and FXTAS (Filley et al , 1999; Schmahmann et al , 2008; Chabriat et al , 2009; Kasuga et al , 2011). …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…White matter dementia is distinguished from cortical dementia, like Alzheimer’s disease, by relative normalcy of language function and declarative memory encoding while cognitive speed, executive function, and sustained attention are impaired (Filley, 1998; Prins et al , 2005). The FAB score decline of NIID cases may reflect the white matter damage, and this pattern of decline is similar to other neurological diseases with white matter damage, such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and FXTAS (Filley et al , 1999; Schmahmann et al , 2008; Chabriat et al , 2009; Kasuga et al , 2011). …”
Section: Discussionmentioning
confidence: 54%
“…Some cases of FXTAS present with dementia and leukoencephalopathy (Kasuga et al , 2011), and eosinophilic ubiquitin-positive intranuclear inclusions are observed in FXTAS in neurons, glial cells and somatic cells, similar to NIID (Gokden et al , 2009; Hagerman, 2013; Buijsen et al , 2014). There is no literature on the skin pathological or electron microscopic findings of intranuclear inclusions in FXTAS.…”
Section: Discussionmentioning
confidence: 99%
“…FXTAS had until recently been considered fundamentally to be a CNS disorder; with principal neuropathologic findings of intranuclear neuronal and astrocytic inclusions [18,41,59,60,85,90], as well as white matter disease and loss of brain volume [1,23,30,60,94,100,7476,162] that point to subtle alterations in brain structure and white matter that may precede overt symptoms of the disorder [12,115]. However, an early indication that the pathology of FXTAS may extend beyond the CNS were the observations that intranuclear inclusions were present in both the anterior and posterior pituitary [61,117], and in testicular Leydig and myoid cells in two men who had died with FXTAS [61].…”
Section: Developments In the Pathology Of Fxtasmentioning
confidence: 99%
“…An interesting finding from a study by Sone et al ( 2016 ) showed that the FAB scores declined more obviously than the MMSE scores, particularly in the dementia-dominant group, whether they were sporadic or not. The decline in the FAB score of NIID cases may reflect the white matter damage, and this pattern of decline is similar to other neurological diseases with white matter damage, such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) (Filley et al, 1999 ; Chabriat et al, 2009 ) and FXTAS (Kasuga et al, 2011 ). Recently, Wang et al ( 2020 ) investigated the executive dysfunction in patients with NIID reflected by Trail Making Test (TMT, For Trail A, the participants were required to connect, as quickly as possible, circles containing numbers in the ascending numerical order.…”
Section: Neuronal Intranuclear Inclusion Diseasementioning
confidence: 61%